The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1088/1748-3190/aa5113
|View full text |Cite
|
Sign up to set email alerts
|

Performance variation due to stiffness in a tuna-inspired flexible foil model

Abstract: Tuna are fast, economical swimmers in part due to their stiff, high aspect ratio caudal fins and streamlined bodies. Previous studies using passive caudal fin models have suggested that while high aspect ratio tail shapes such as a tuna's generally perform well, tail performance cannot be determined from shape alone. In this study, we analyzed the swimming performance of tuna-tail-shaped hydrofoils of a wide range of stiffnesses, heave amplitudes, and frequencies to determine how stiffness and kinematics affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…For example, understanding how body shape influences swimming specializations [ 5 , 6 ], how material properties of the body dictate swimming performance [ 7 – 11 ], and the relative contributions of individual fins to overall movement [ 12 , 13 ] all remain largely unresolved issues in the study of aquatic locomotion. While many approaches, including computational (e.g., [ 9 , 13 ]), physical modeling (e.g., [ 7 , 11 , 14 , 15 ]), and experimental (e.g., [ 12 , 16 , 17 ]), can be taken to answer these questions, one promising approach is to leverage a detailed understanding of the magnitudes and distributions of the time-varying forces and torques that fishes generate to effect locomotion [ 18 21 ]. Despite the value of this information for understanding biological swimming, fish evolution, and developing bioinspired underwater vehicles, the nature of a fish’s fluid environment renders direct measurements of forces and torques impractical.…”
Section: Introductionmentioning
confidence: 99%
“…For example, understanding how body shape influences swimming specializations [ 5 , 6 ], how material properties of the body dictate swimming performance [ 7 – 11 ], and the relative contributions of individual fins to overall movement [ 12 , 13 ] all remain largely unresolved issues in the study of aquatic locomotion. While many approaches, including computational (e.g., [ 9 , 13 ]), physical modeling (e.g., [ 7 , 11 , 14 , 15 ]), and experimental (e.g., [ 12 , 16 , 17 ]), can be taken to answer these questions, one promising approach is to leverage a detailed understanding of the magnitudes and distributions of the time-varying forces and torques that fishes generate to effect locomotion [ 18 21 ]. Despite the value of this information for understanding biological swimming, fish evolution, and developing bioinspired underwater vehicles, the nature of a fish’s fluid environment renders direct measurements of forces and torques impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have calculated the denominator of (2.8) for pitching fins (input power) as the period-averaged product of torque and angular velocity at the base (Dewey et al 2013;Lucas et al 2015Lucas et al , 2017Quinn et al 2015;Egan, Brownell & Murray 2016;David et al 2017;Floryan et al 2017;Rosic et al 2017;Zhu et al 2017). This efficiency metric is appropriate for hydrodynamic experiments where forces and torque sensors are placed at the attachment rod of the flapping propulsor.…”
Section: Calculationsmentioning
confidence: 99%
“…In the past decade, the field has divided into two groups that focus on either two-dimensional models for parametric studies or three-dimensional models with fewer cases. Within the two-dimensional group, there has been a recent push to understand fish propulsion through nondimensional scaling with a symmetric airfoil representing the caudal fin [10][11][12][13] or a flexible thin foil representing the undulating fish body [14][15][16]. Within the three-dimensional group, there are physical systems that mimic the motions of fish [17][18][19] as well as numerical works that investigate the fluid dynamics around full fish models [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of body kinematics has also been shown to be important [14][15][16]22,23,[33][34][35][36]. Wu analytically found that a flexible two-dimensional panel deforming with a transverse traveling wave is preferable to a rigid panel [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation